Echocardiography in acute critical care in cardiology - N.D. Oryshchyn (Кардіохірургія та інтервенційна кардіологія)
Diagnostic opportunities of echocardiography in the acute cardiac care are reviewed. It is shown in detail how to perform echocardiography in different scenarios of critical conditions, especially in acute chest pain, acute hypotension and shock, in acute dyspnoea, in chest trauma, in post-procedural and post-surgical complications. The advantages and disadvantages of the echocardiographic method in acute myocardial infarction with complications, in acute aortic dissection, in cardiac tamponade, in pulmonary embolism, in systolic left ventricular dysfunction and in acute valvular dysfunction are analyzed.